EU terrorism situation and trend report TE-SAT / EUROPOL / 2013 (EU terrorism situation and trend report TE-SAT, 2013)
The TE-SAT is one of Europol's most significant strategic analysis products. It offers law enforcement officials, policymakers and the general public facts and figures regarding terrorism in the EU while, at the same time, seeking to identify developing trends in this phenomenon. It is a public document produced annually and is based on information provided and verified by the competent authorities of the EU Member States. This and previous editions of the TE-SAT reports are available on Europol's website: www.europol.europa.eu.